Question Error Report

Thank you for reporting, we will resolve it shortly

Back to Question

Q. Let $S=\left\{x: x \in R\right.$ and $\left.(\sqrt{3}+\sqrt{2})^{x^2-4}+(\sqrt{3}-\sqrt{2})^{x^2-4}=10\right\}$. Then $n(S)$ is equal to

JEE MainJEE Main 2023Complex Numbers and Quadratic Equations

Solution:

Let $(\sqrt{3}+\sqrt{2})^{x^2-4}= t$
$ t +\frac{1}{ t }=10$
$\Rightarrow t =5+2 \sqrt{6}, 5-2 \sqrt{6} $
$\Rightarrow (\sqrt{3}+\sqrt{2})^{ x ^2-4}=5+2 \sqrt{6}, 5-2 \sqrt{6} $
$\Rightarrow x ^2-4=2,-2 \text { or } x ^2=6,2 $
$\Rightarrow x =\pm \sqrt{2}, \pm \sqrt{6}$